Optimisation of sports performance using computer simulation models - King, M.; Yeadon, M.; Kong, P. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume II: Bio-Mechanics and Sports Engineering., 2008)
Computer simulation models are often used to optimise performance of whole body movements. This paper investigates the factors that influence optimum performance, whether strength limits performance, how a consistent performance is achieved and the effect of anatomical constraints on optimum performance. Three whole body torque driven forward dynamics computer simulation models are developed for Ihe takeoff phase in vaulting, tumbling and springboard diving. Subject-specific parameters are determined for each model based upon experimental data on each elite athlete and the models are evaluated by comparing simulations with performances. Simulations and optimisations are then used to investigate optimum performance. The initial conditions at touchdown with the vaulting horse are found to be very important with it being impossible to complete some vaults if the initial conditions are inappropriate. A realistic optimum tumbling simulation is only obtained when timing perturbations during the takeoff phase are incorporated within the optimisation process. Furthermore realistic optimum simulations for maximising rotation from the 1 m springboard are only obtained when constraints are included within the optimisation process to prevent the model from exceeding anutomical ranges of motion.